The role of social media in improving the transparency of village fund management - Yose Rizal; Eka Siskawati (Entrepreneurship and Small Business Research, 2022)
The village financial management aims to account for the use of the budget to realize good governance. Village financial management must be carried out openly, and the information presented can be accessed by the public. The information presented must show accountability for a village official's performance to the authorities who obtain the information. However, there is still a management crisis in managing village funds caused by the unsatisfactory performance of village officials. One of the unsatisfactory performances was motivated by the competence of village officials, who were still not following the expected standards. Kumanis village was named the most transparent Village in West Sumatra. In this article, Kumanis village's success in implementing aspects of openness and transparency in financial management is explored in depth. With an inductive qualitative approach, data were collected through in-depth interviews, field observations, and focus group discussions. This study found that transparency in financial management was carried out by involving the people of Kumanis Village. Village meetings are used as a communication forum for village officials to accommodate and resolve community complaints against the performance of the Village government. In addition, social media and mass media are optimized to publish Village activities to all levels of society. This research provides implications for tactical practices in improving the principles of transparency, accountability, and participation in village financial management.